Beneficial Effects of High-Intensity Interval Training and Dietary Changes Intervention on Hepatic Fat Accumulation in HFD-Induced Obese Rats - Yuan, X-M; Xiang, M-Q; Ping, Y; Zhang, P-W; Liu, Y-T; Liu, X-W; Wei, J; Tang, Q; Zhang, Y (Physiological research, 2024)
Lifestyle intervention encompassing nutrition and physical activity are effective strategies to prevent progressive lipid deposition in the liver. This study aimed to explore the effect of dietary change, and/or high-intensity interval training (HIIT) on hepatic lipid accumulation in high fat diet (HFD)-induced obese rats. We divided lean rats into lean control (LC) or HIIT groups (LH), and obese rats into obese normal chow diet (ND) control (ONC) or HIIT groups (ONH) and obese HFD control (OHC) or HIIT groups (OHH). We found that dietary or HIIT intervention significantly decreased body weight and the risk of dyslipidemia, prevented hepatic lipid accumulation. HIIT significantly improved mitochondrial fatty acid oxidation through upregulating mitochondrial enzyme activities, mitochondrial function and AMPK/PPARalpha/CPT1alpha pathway, as well as inhibiting hepatic de novo lipogenesis in obese HFD rats. These findings indicate that dietary alone or HIIT intervention powerfully improve intrahepatic storage of fat in diet induced obese rats. Keywords: Obesity, Exercise, Diet, Mitochondrial function, Lipid deposition.
Keywords: High-Intensity Interval Training; Liver; kondiční příprava zvířat; Rats; játra; Physical Conditioning, Animal; Obesity; potkani Sprague-Dawley; mužské pohlaví; Diet, High-Fat; vysoce intenzivní intervalový trénink; dieta s vysokým obsahem tuků; krysa rodu Rattus; Lipid Metabolism; zvířata; metabolismus lipidů; obezita; Rats, Sprague-Dawley; Male; Animals